Nanomedicine and nanobiotechnology - Logothetidis, Stergios (NanoScience and Technology, 2012)
This book presents the laboratory, scientific and clinical aspects of nanomaterials used for medical applications in the fields of regenerative medicine, dentistry and pharmacy. It gives a broad overview on the in vitro compatibility assessment of nanostructured materials implemented in the medical field by the combination of classical biological protocols and advanced non-destructive nano-precision techniques with special emphasis on the topographical, surface energy, optical and electrical properties. Materials in the physical form of nanoparticles, nanotubes, and thin films are addressed in terms of their toxicity. The different pillars of the Nanomedicine field are also highlighted. The book takes an interdisciplinary approach of medicine, biology, pharmacy, physics, chemistry, engineering, nanotechnology and materials science. The international group of authors specifically chosen for their distinguished expertise belong to the academic and industrial world in order to provide a broader perspective. It appeals to researchers and graduate students.